Survival Strategies of Klang Valley Malaysian Small and Medium Building Contractors in the Post-Covid-19 Era - Toh, Tien Choon; Chong, Yaw Chien; Lew, Yoke Lian; Goh, Kai Chen; Zainordin, Nadzirah; Lee, Chia Kuang (Construction Research Institute of Malaysia, 2023)
The post-COVID-19 era in Malaysia’s busiest area, Klang Valley, necessitates an examination of the survival strategies used by small and medium building contractors in the construction industry, which are numerous in a developing country like Malaysia and contribute significantly to the country’s economy. As a result, the purpose of this study was to investigate the survival strategies and perceived success of Klang Valley Malaysian small and medium building contractors in the post-COVID-19 era, to uncover the strategies that would ensure the small and medium building contractors’ continuous survival. In this study, a survey approach was used, and building contractors in six grades ranging from G1 to G6 of CIDB Malaysia registered building contractors were sampled using a structured questionnaire. Mean ranking and factor analysis were used to analyse the data collected. The top five important survival strategies were as follows: (1) effective financial management, (2) upgrading of the skills of employees for productivity improvement, (3) improvement of service quality performance, (4) improvement of problem-solving capabilities, and (5) efficient marketing. The factor analysis method was used to identify the underlying factors of survival strategies such as diversification, networking, and innovation strategies; workforce management strategies; and financial management strategies. The effects of organisational survival on small and medium building contractors’ perceived success in terms of business growth, profit growth, and employment growth were also investigated. This study raised awareness and deepened our understanding of the survival strategies used by Klang Valley Malaysian small and medium building contractors, as well as how their organisational survival was perceived.